PERENCANAAN PEMELIHARAAN DAN OPTIMASI BIAYA PERAWATAN PADA SISTEM UTILITY DENGAN METODE PREVENTIVE MAINTENANCE - Zainal Arifin Muhammad; Haryono Edi; Arumsari Nurvita (Proceedings Conference on Marine Engineering and its Application, 2018)
A company oil refinery based on condensate or petroleum using corrective maintenance type, one of them is in utility system. Corrective maintenance is less suitable with the course of production in a company it is continuous because the company can lose due to production stopped. Therefore, reliability analysis is performed using preventive maintenance method the scheduling check or inspection is used to prevent machinery or equipment from being damaged. Thus, the performance of the machine can run smoothly so that the production process is not disrupted and more efficient. Cost operational from 2011-2017 will be identified failure with FTA and FMEA. So that will get the value of reliability. Then performed the scheduling in accordance with the resulting MTTF value. Then the cost will be calculated to produce more efficient maintenance cost and the result more efficient cost is 30%.